Application of the Canvas model for the creation of a software factory in a public university: Case study UNFV - FIIS - Muñoz Ramos, Luis Avelino (2023)
This research aimed to use the Canvas Business Model to establish an academic software factory at Universidad Nacional Federico Villarreal - Facultad de Ingeniería Industrial y de Sistemas (UNFV-FIIS). As a public university with financial limitations, five of the nine blocks  composing the model were relevant: value proposition, customer segment, customer relationships, key activities, and key resources. Named faculty members from the Department of Systems Engineering and students enrolled in the Professional School of Systems Engineering 2022 software engineering courses were selected to identify the five blocks of the model. Surveys were conducted among faculty members and students to gather information on the current situation, requirements, and expectations regarding creating an academic software factory. The collected data was analyzed using the Canvas model, focusing on the value proposition and identifying differentiating characteristics. The study highlights the importance of applying modern models and standards for software development and quality. In conclusion, the Canvas business model establishes a relationship between the needs and expectations of faculty members and students and the services provided by the software factory.